Countries and Regions Dynamic Interconnectivity - Yang, Guang; Zhang, Jing; Liu, Lanyu; Xiong, Xinghan (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2024)
XXV, 338 p. 46 illus., 32 illus. in color.